Spatial stability of slope cuts in rock massifs using GIS technology and probabilistic analysis - Irigaray, C.; El Hamdouni, R.; Jiménez-Perálvarez, J. D.; Fernández, P.; Chacón, J. (Bulletin of engineering geology and the environment, 2012)
This paper presents a methodology for the stability analysis of cuts in rock slopes. A kinematic analysis of the different types of failure (planar, wedge, and toppling) is developed using GIS, following which a probabilistic analysis is made of the limit equilibrium in slopes where the conditions for kinematic failure are satisfied. The results were verified by comparing the evaluation against the observed stability conditions in 40 road cuts along 4 km of national road N-340, on the Mediterranean edge of Granada province (southern Spain). The validation analysis showed that for some 90% of the slopes studied there was a reasonable fit between the observed and evaluated stability, indicating the proposed methodology is suitable for the preliminary analysis of the stability conditions on rock slopes.